Model Sustainability and Financial Performance of SME in Bali - Putu Cita Ayu; Ni Putu Trisna Windika Pratiwi; Rai Dwi Handayani (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
This research aims to build a model of sustainability practices in improving the financial performance of SMEs in Bali by analyzing the role of sustainability performance as a mediator and the role of environmental policy as a moderator of green innovation towards sustainable practices of SMEs in Bali. This study uses a quantitative method with a survey design. The survey was conducted on 390 SMEs in Bali. The questionnaire was distributed directly to SME managers using stratified random sampling. Hypothesis testing was carried out using the SEM-PLS approach with the help of SmatPLS.3.0 software. The results of the study indicate that the variables of green innovation, sustainability performance and environmental policy directly affect the financial performance. These findings fully support stakeholder theory, RBV theory and legitimacy theory. This study also found the role of sustainability performance in mediating the relationship between green innovation and financial performance. In addition, it was also found that environmental policy plays a role in moderating the relationship between green innovation and sustainability performance with financial performance. The results of this study reaffirm that sustainability performance can improve financial performance when companies involve the adoption of green technologies and practices.